Evidence update for the treatment of anaphylaxis. (June 2021) - Dodd, Amy; Hughes, Anna; Sargant, Nicholas; Whyte, Andrew F.; Soar, Jasmeet; Turner, Paul J.
Abstract: The Resuscitation Council UK has updated its Guideline for healthcare providers on the Emergency treatment of anaphylaxis. As part of this process, an evidence review was undertaken by the Guideline Working Group, using an internationally-accepted approach for adoption, adaptation, and de novo guideline development based on the Grading of Recommendations Assessment, Development and Evaluation (GRADE) evidence to decision (EtD) framework, referred to as GRADE-ADOLOPMENT. A number of significant changes have been made, which will be reflected in the updated Guideline. These include: emphasis on repeating intramuscular adrenaline doses after 5 min if symptoms of anaphylaxis do not resolve; corticosteroids (e.g. hydrocortisone) no longer being routinely recommended for the emergency treatment of anaphylaxis; interventions for reactions which are refractory to initial treatment with adrenaline; a recommendation against the use of antihistamines for the acute management of anaphylaxis; and guidance relating to the duration of observation following anaphylaxis, and timing of discharge.